Pelatihan Pembuatan LKPD Inovatif Berbasis Discovery Learning Menggunakan Edform Materi Sudut Kelas V - Erika Rahmawati; Linda Apriyani; Ambaryani Siwi Nugraheni; Putri Zudhah Ferryka (Jurnal Informasi Pengabdian Masyarakat, 2024)
Technological developments greatly influence several aspects of life. These aspects can include education, economics, culture and politics. An educator must prepare several abilities in applying learning activities. So that the learning process is not monotonous and varied. This ability is in the form of an educator's ability in terms of technology. This service aims to increase the insight and creativity of students, especially PGSD students, in carrying out innovative learning activities. The methods used in the service are in the form of demonstrations, lectures and direct practice using their respective laptops. The result of this service is the opening of new insights for students regarding technological developments that can be used in the world of education.